Omental transplantation for an injury in the sciatic nerve - Cruz, Hernando Rafael (2010)
Clinical case: A 26-year old woman had a 6-month history of motor and sensorial loss in her right foot and leg after undergoing a hip replacement surgery. Two electro-diagnostic studies revealed absence of nerve conduction in tibial, fibular, and sciatic nerves. Six moths afterwards, the patient underwent an omental transplantation in the damaged area of the right sciatic nerve. Results: Neurological improvement occurred from the second day after surgery. Nowadays, two years after surgery, the patient has mild to moderate paralysis and hypoesthesia in her right foot and leg. The patient is able to walk using orthopedic support. Conclusion: These results indicate that with this surgical approach we may be able to get over the sequels caused by ischemia and/or trauma in the sciatic nerve; and probably this may also apply to the brachial plexus.